Unconventional Computation and Natural Computation 12th International Conference, UCNC 2013, Milan, Italy, July 1-5, 2013. Proceedings - Mauri, Giancarlo; Dennunzio, Alberto; Manzoni, Luca.; Porreca, Antonio E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 12th International Conference on Unconventional Computation and Natural Computation, UCNC 2013, held in Milan, Italy, in July 2013. The 30 papers (28 full papers, 8 poster papers, and 2 invited papers) were carefully reviewed and selected from 46 submissions. The topics of the volume include: quantum, cellular, molecular, neural, DNA, membrane, and evolutionary computing; cellular automata; computation based on chaos and dynamical systems; massive parallel computation; collective intelligence; computation based on physical principles such as relativistic, optical, spatial, collision-based computing; amorphous computing; physarum computing; hypercomputation; fuzzy and rough computing; swarm intelligence; artificial immune systems; physics of computation; chemical computation; evolving hardware; the computational nature of self-assembly, developmental processes, bacterial communication, and brain processes.
Quantum, cellular, molecular, neural, DNA -- Membrane, and evolutionary computing -- Cellular automata -- Computation based on chaos and dynamical systems -- Massive parallel computation -- Collective intelligence -- Computation based on physical principles such as relativistic -- Optical, spatial, collision-based computing -- Amorphous computing -- Physarum computing -- Hypercomputation -- Fuzzy and rough computing -- Swarm intelligence -- Artificial immune systems -- Physics of computation -- Chemical computation -- Evolving hardware -- The computational nature of self-assembly, developmental processes, bacterial communication, and brain processes.
Keywords: Computer science; Computers; Algorithms; Mathematical logic; Artificial intelligence; Computer simulation; Bioinformatics; Computer Science; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Mathematical Logic and Formal Languages; Artificial Intelligence (incl. Robotics).; Simulation and Modeling; Computational Biology/Bioinformatics.; Electronic books